Diagnosis and management of mesiodens based on the investigation of its position using cone-beam computed tomography. Issue 2 (August 2016) - Itaya, Satoshi; Oka, Kyoko; Kagawa, Toyohiro; Oosaka, Yosuke; Ishii, Kaori; Kato, Yoko; Baba, Atsuko; Ozaki, Masao
Abstract: Background: The presence of mesiodens induces various occlusal and pathological complications. Hence, early extraction of mesiodens is required to prevent them. It is difficult to decide the appropriate time for mesioden extraction because the close relation of the developing root of the permanent incisors with mesiodens, and patient's cooperation for operation have to be considered. Therefore, we need to evaluate the criteria to decide the appropriate extraction timing of mesiodens. This study was carried out to indicate the position of mesiodens among age and developmental stages of central incisors (Nolla's classification). Methods: A total of 290 mesiodens were examined in 242 patients, and their positions were measured using cone-beam computed tomography images. Finally, 259 mesiodens were analyzed after excluding mesiodens in horizontal directions and/or in buccal side orientation. Results: In normal directions, the distance from the alveolar crest and maxillary bone surface to mesioden did not change with age and Nolla's classification, but that from the root apex of the developing incisor was decreased. Conversely, mesiodens in inverted directions tended to be located deeper, higher in maxillae and closer to the root apex of the incisor with age and Nolla's classification. The position of mesiodens in inverted direction showed statistic correlational with age and Nolla's classification. Furthermore, we suggest a radar chart for the diagnosis and the speculation to the position of mesiodens at present and future, objectively. Conclusion: Our results will be helpful when deciding on the timing of mesioden extraction with minimum stress and risk for children.